(untitled) (Bangladesh Medical Journal, 2014)
This cross sectional study was carried out among 146 garment workers from selected two garments industries to find out the magnitude of Hepatitis B virus infection in Narayangonj. Data was collected through face to face interview of the workers by using a pre tested questionnaire. The study was conducted during April to June 2007.Majority 56.2% were in the age group of 18-25 years followed by 32.9% were of 26-35 years. By sex partner majority 28.8% had their partnership with their husband, 11% had partnership with their wife and 2. 7% had sexual relation with their boyfriend and 5.5% had relation with their girlfriend, 8. 9% had history of sex with commercial sex worker. In this study only 11 (7.5%) respondents had HBV positive. Among them who had the history of inject able drug taking 8(2.05%) were found positive. Statistically it was found highly significant. History of jaundice, only 1 (0.7%) respondents had HBV positive while those who had no history of jaundice 10 (6.8%) had HBV positive. In this study it was found that 6(46.2%) HBV positive respondents who had sex with commercial sex worker and none of the respondents those who had sex with their wife were HBV negative. This was found statistically significant, that means development of hepatitis B virus might has an association of sex with sex worker. The study recommended mass screening of hepatitis should be conducted among the garments workers as it was found highly prevalence among the study workers. DOI: http://dx.doi.org/10.3329/bmj.v40i2.18511 Bangladesh Medical Journal 2011 Vol.40(2): 50-53